FeOOH / C ortho-parahydrogen conversion catalyst and preparation method thereof

Through the preparation of FeOOH/C positive and secondary hydrogen conversion catalyst, the problems of high catalyst cost, low activity and high density in the prior art are solved, and the efficient positive and secondary hydrogen conversion effect is achieved, and low-cost and high-performance catalyst solutions are provided. plan.

CN119158570AActive Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310700880.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-20
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The existing supported positive secondary hydrogen conversion catalysts have problems such as high preparation cost, low active metal content, large bulk density and poor catalytic effect.

Method used

Using FeOOH/C positive secondary hydrogen conversion catalyst, Fe/C complex is formed in the solvothermal reaction through iron salts, organic ligands and organic polymers, and liquid phase oxidation is carried out in the presence of an oxidant to form a high metal content. Supported catalysts avoid the existence of harmless elements.

Benefits of technology

A catalyst with low cost, uniform distribution of high active components and low stacking density is achieved, which significantly improves the conversion effect of secondary hydrogen, and avoids the problems of catalyst damage and blocking the bed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158570A_ABST
    Figure CN119158570A_ABST
Patent Text Reader

Abstract

The invention discloses a FeOOH / C ortho-parahydrogen conversion catalyst and a preparation method thereof, the FeOOH / C ortho-parahydrogen conversion catalyst has the FeOOH mass content of 30-90%, the specific surface area of 150-750 m < 2 > / g, the particle size of 20-60 meshes, and the bulk density of 0.2-0.8 g / mL. The preparation method comprises the following steps: (1) uniformly mixing ferric salt, an organic ligand, an organic high-molecular polymer and a solvent by mass to obtain a precursor mixture; (2) performing solvothermal reaction and solid-liquid separation on the precursor mixture in a closed container, performing vacuum drying on solid particles, and then roasting in an inert atmosphere to obtain a Fe / C compound; (3) adding the Fe / C compound into a proper amount of an aqueous solution containing an oxidant, and carrying out a liquid-phase oxidation reaction under a closed condition until the liquid-phase oxidation reaction is fully carried out; and (4) washing, drying, crushing and screening the obtained product to obtain the supported ortho-parahydrogen conversion catalyst with the FeOOH / C structure. The catalyst has the advantages of low preparation cost, simple production process, low material flow resistance and good catalytic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid hydrogen, and specifically relates to a FeOOH / C ortho-parahydrogen conversion catalyst and a preparation method thereof. Background Art

[0002] A hydrogen molecule is composed of two hydrogen atoms with different nuclear spin directions, of which the one with symmetric nuclear spin is orthohydrogen and the one with antisymmetric nuclear spin is parahydrogen. Both orthohydrogen and parahydrogen can exist stably in liquid and gaseous states. The equilibrium concentration of orthohydrogen and parahydrogen in hydrogen is affected by temperature. At room temperature, the content of orthohydrogen in hydrogen is 25%, and the content of parahydrogen is 75%, which is called normal hydrogen or standard hydrogen. When the temperature drops, orthohydrogen will spontaneously convert to parahydrogen. At the standard boiling point of liquid hydrogen, the content of parahydrogen can reach 99.8%. In the absence of an external catalyst, the spontaneous conversion of the orthohydrogen to the parahydrogen state is very slow, and the conversion process is accompanied by the release of heat, which is greater than the heat of vaporization of liquid hydrogen, causing a large amount of stored liquid hydrogen to vaporize. In a liquid hydrogen storage tank, if there is no catalyst, the heat released by the reaction causes the liquid hydrogen to vaporize continuously, thereby consuming the liquid hydrogen. In order to complete the conversion of orthohydrogen to parahydrogen while liquefying hydrogen, a high-performance low-temperature orthohydrogen conversion catalyst is essential for the production and storage of liquid hydrogen.

[0003] CN112844443 A uses ordered mesoporous materials such as MCM-41, SBA-15, MCM-48 and CMK-3 as carriers, uses chemical precipitation method to impregnate, roast and then shape to obtain a supported normal-parahydrogen conversion catalyst, but the ordered mesoporous carrier material used in the method is expensive and complicated to prepare, resulting in excessively high catalyst cost. The inorganic carrier used often has a large bulk density, which is easy to cause catalyst damage and block the bed.

[0004] CN 112044457 A uses an impregnation method to load metal active substances on the surface of a non-metal modified porous carrier to obtain a supported normal-parahydrogen conversion catalyst. The preparation process is simple, but the metal oxide content obtained by the method is only 5-30%, the active metal content is low, and the catalytic effect is significantly reduced at high space velocity; the surface acidity of the carrier is regulated by the introduced phosphorus, chlorine and fluorine ions to improve the uniformity of the active component loading, but the loss of the above ions in the prepared catalyst during use will lead to deterioration of the liquid hydrogen quality and adverse effects on the reactor. The inorganic carrier used generally has a large bulk density, which is easy to cause catalyst damage and block the bed.

[0005] Existing supported ortho-parahydrogen conversion catalysts have the problems of high preparation cost, low active metal content, high bulk density, and poor catalytic effect. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention proposes a FeOOH / C ortho-parahydrogen conversion catalyst and a preparation method thereof. The obtained catalyst has low material flow resistance, good catalytic effect, low preparation cost and simple production process.

[0007] The FeOOH / C ortho-parahydrogen conversion catalyst of the present invention comprises, based on the mass of the catalyst, 10% to 70% of a carbon carrier and 30% to 90% of FeOOH, wherein the FeOOH content is preferably 70% to 90%; the Fe element is evenly distributed on the carbon carrier, and the specific surface area is 150 to 750 m 2 / g, particle size 20-60 mesh, bulk density 0.2-0.8g / mL.

[0008] The preparation method of the FeOOH / C ortho-parahydrogen conversion catalyst of the present invention comprises the following contents: (1) uniformly mixing an iron salt, an organic ligand, an organic high polymer and a solvent by mass to obtain a precursor mixture; (2) placing the precursor mixture in a sealed container for a solvothermal reaction, cooling to room temperature after the reaction, separating the solid and the liquid, vacuum drying the solid particles, and then calcining them in an inert atmosphere to obtain a Fe / C composite; (3) adding the Fe / C complex to an appropriate amount of aqueous solution containing an oxidant under closed conditions until the liquid phase oxidation reaction is fully carried out; (4) Washing, drying, crushing and screening the obtained product to obtain a supported normal-parahydrogen conversion catalyst with a FeOOH / C structure.

[0009] In the method of the present invention, the material ratios in step (1) are, by weight, 1-10 parts of iron salt, 0.5-20 parts of organic ligand, 2-50 parts of organic high molecular polymer, and 50-150 parts of solvent.

[0010] In the method of the present invention, the iron salt in step (1) is one or more of ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric nitrate or ferrous nitrate.

[0011] In the method of the present invention, the organic ligand in step (1) is one of fumaric acid, terephthalic acid, aminoterephthalic acid, trimesic acid, aminoimidazole or 2-methylimidazole, or a mixture thereof in any proportion.

[0012] In the method of the present invention, the solvent in step (1) is ethanol, N,N-dimethylformamide, dimethyl sulfoxide or water or a mixture thereof in any proportion.

[0013] In the method of the present invention, the organic high molecular polymer in step (1) is one of polyvinyl pyrrolidone, polymethyl acrylate, chitosan, polyacrylic acid, sodium citrate, sodium oleate, polyethylene glycol or polyethylene glycol with carboxyl groups at both ends, or a mixture thereof in any proportion.

[0014] In the method of the present invention, the reaction temperature of the solvent thermal reaction in step (2) is 60-230°C, the reaction time is 3-30 hours, and the pressure is autogenous. The preferred conditions for the solvent thermal reaction are: reaction temperature 120-200°C, reaction time 5-24 hours, and reaction pressure is autogenous pressure.

[0015] In the method of the present invention, the solid-liquid separation in step (2) can be carried out by filtering, centrifuging, natural precipitation or the like to remove impurities, and the solvent used for washing is one or more of water, anhydrous ethanol, methanol and heptane.

[0016] In the method of the present invention, the vacuum drying temperature in step (2) is 60-150°C, the vacuum drying time is 6-30 hours, and the vacuum degree is (-0.1)-(-8) kPa. More preferably, the vacuum drying temperature is 80-130°C, and the vacuum drying time is 10-16 hours.

[0017] In the method of the present invention, the calcination temperature in step (2) is 350-900°C, and the calcination time is 10-200 minutes. The calcination conditions are preferably 450-650°C, and the calcination time is 20-100 minutes.

[0018] In the method of the present invention, the inert atmosphere in step (2) is an inert gas and / or nitrogen.

[0019] In the method of the present invention, the oxidant in step (3) is hydrogen peroxide and / or peracetic acid.

[0020] In the method of the present invention, in step (3), the mass ratio of the Fe / C complex to the oxidant is 1:1 to 5. The mass concentration of the oxidant used is 1-30%, preferably 5-15%.

[0021] In the method of the present invention, the liquid phase oxidation conditions of the Fe / C complex and the oxidant in step (3) are: under autogenous pressure, reaction temperature 10-150°C, reaction time 1-24 hours, preferably reaction temperature 20-100°C, reaction time 2-12 hours.

[0022] In the method of the present invention, the drying conditions of the catalyst in step (4) are: drying temperature 80-180°C, drying time 3-48 hours, preferably drying temperature 120-150°C, drying time 12-24 hours. The drying conditions are further preferably vacuum drying, with a vacuum degree of (-0.1)-(-8) kPa, a drying temperature of 120-150°C, and a drying time of 6-12 hours.

[0023] The present invention prepares an iron-based metal organic framework material from an iron salt and an organic ligand, and then burns it to obtain a Fe / C composite framework material with a high metal content. After moderate liquid phase oxidation, the Fe in the Fe / C framework material is converted into hydrated iron oxide FeOOH, thereby forming a supported para-hydrogen conversion catalyst with a high metal content and carbon as a carrier. The material has an excellent para-hydrogen catalytic conversion effect.

[0024] The FeOOH / C ortho-parahydrogen conversion catalyst of the present invention has high active component content and uniform distribution, low bulk density, does not contain harmful elements such as sodium, phosphorus, chlorine and fluorine ions, and has high catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the X-ray diffraction pattern of the para-hydrogen conversion catalyst prepared in Example 1 of the present invention.

[0026] Figure 2 This is the X-ray diffraction pattern of the para-hydrogen conversion catalyst prepared in Comparative Example 1 of the present invention.

[0027] Figure 3 This is the iron element distribution diagram of the para-hydrogen conversion catalyst prepared in Example 1 of the present invention (the white dots represent the iron element). DETAILED DESCRIPTION

[0028] The FeOOH content of the catalyst of the present invention is determined by using hydrochloric acid to dissolve the catalyst, separating the insoluble matter to obtain the carbon carrier, and then calculating the FeOOH content according to the weight difference before and after dissolution. The specific surface area is tested by the BET method. The bulk density is determined according to SH / T 0958-2017 Molded Catalyst and Catalyst Carrier Mechanical Vibration Bulk Density Determination Method. Example 1

[0029] According to the mass ratio, 1 part of ferric nitrate 9hydrate, 0.5 parts of trimesic acid and 10 parts of polyethylene glycol were mixed with 100 parts of anhydrous ethanol, water and N,N-dimethylformamide in a volume ratio of 1:1:1. The mixture was placed in a reactor and reacted at 150°C for 10 hours and cooled to room temperature. The product was alternately treated with water and methanol, centrifuged to obtain solid particles, which were vacuum dried at 80°C for 12 hours and then calcined at 450°C in an argon atmosphere for 30 minutes to obtain a Fe / C complex. The obtained Fe / C complex was added to 15% hydrogen peroxide (the mass ratio of the two was 1:2) and soaked at 60°C for 5 hours, then washed with water and filtered, and dried at 120°C for 10 hours. The supported normal-parahydrogen conversion catalyst with a FeOOH / C skeleton structure of 30-40 mesh was obtained by sieving. The FeOOH mass content of the obtained catalyst was 88%, the crushing strength was 8-15N / particle, and the specific surface area of ​​the material was 688m 2 / g, and the bulk density is 0.4g / mL. The test results of the normal-parahydrogen conversion performance of the obtained catalyst are shown in Table 1. Example 2

[0030] According to the mass ratio, 1 part of ferric chloride hexahydrate, 1 part of terephthalic acid and 10 parts of polyvinyl pyrrolidone were mixed evenly with 100 parts of N, N-dimethylformamide. The mixture was placed in a reactor and reacted at 180°C for 10 hours and cooled to room temperature. The product was alternately treated with water and ethanol, centrifuged to obtain solid particles, and after vacuum drying at 60°C for 18 hours, it was urgently calcined at 550°C in an argon atmosphere for 20 minutes to obtain a Fe / C complex. The obtained Fe / C complex was added to 15% hydrogen peroxide (the mass ratio of the two was 1:2) and soaked at 60°C for 5 hours, then washed with water and filtered, and dried at 140°C for 8 hours, and sieved to obtain a 30-40 mesh FeOOH / C skeleton structure supported normal-parahydrogen conversion catalyst. The FeOOH mass content of the obtained catalyst was 85%, the crushing strength was 6-13N / particle, and the specific surface area of ​​the material was 539m 2 / g, and the bulk density is 0.5g / mL. The test results of the normal-parahydrogen conversion performance of the obtained catalyst are shown in Table 1. Example 3

[0031] According to the mass ratio, 1 part of ferrous sulfate nonahydrate, 1 part of benzenetricarboxylic acid and 12 parts of sodium citrate were mixed evenly with 100 parts of ethylene glycol. The mixture was placed in a reactor and reacted at 150°C for 15 hours and cooled to room temperature. The product was alternately treated with water and ethanol, centrifuged to obtain solid particles, and after vacuum drying at 80°C for 10 hours, it was urgently calcined at 450°C in an argon atmosphere for 60 minutes to obtain a Fe / C complex. The obtained Fe / C complex was added to 15% hydrogen peroxide (the mass ratio of the two was 1:2) and soaked at 60°C for 5 hours, then washed with water and filtered, and dried at 130°C for 15 hours, and sieved to obtain a 30-40 mesh FeOOH / C skeleton structure supported normal-parahydrogen conversion catalyst. The mass content of FeOOH in the obtained catalyst was 89%, the crushing strength was 6-15N / particle, and the specific surface area of ​​the material was 615m 2 / g, and the bulk density is 0.3g / mL. The test results of the normal-parahydrogen conversion performance of the obtained catalyst are shown in Table 1.

[0032] Comparative Example 1 Example 2 in CN 112044457A.

[0033] Comparative Example 2 Example 1 in CN112844443 A. Example 4

[0034] The prepared catalyst was loaded into a reaction tube, activated, and completely immersed in a liquid nitrogen bath. After the temperature stabilized, the chromatograph was connected. The space velocity of hydrogen passing through the reaction tube was adjusted until the flow meter reading was stable, and the area of ​​the parahydrogen peak at different space velocities was measured, and the measurement was repeated 3 times. The parahydrogen content after catalysis at different space velocities was calculated according to the parahydrogen content calculation formula in GB / T 40045-2021. The test results of the normal parahydrogen conversion performance of the obtained catalyst are shown in Table 1.

[0035] Table 1 Parahydrogen conversion rate (%) Results

[0036] Airspeed L / L / min Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 50 100 99.9 100 100 99.9 300 97.6 97.7 97.6 96.3 96 600 95.7 95.9 95.4 94.1 94.5 The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A FeOOH / C ortho-parahydrogen conversion catalyst, characterized in that: Based on the mass of the catalyst, it includes: 10wt%~70wt% of the carbon carrier and 30wt%-90wt% of FeOOH.

2. The catalyst according to claim 1, characterized in that: The FeOOH content is 70wt%-90wt%.

3. The catalyst according to claim 1, characterized in that: The Fe element is evenly distributed on the carbon carrier.

4. The catalyst according to claim 1, characterized in that: Specific surface area 150-750m 2 / g, particle size 20-60 mesh, bulk density 0.2-0.8g / mL.

5. A method for preparing the FeOOH / C ortho-parahydrogen conversion catalyst according to any one of claims 1 to 4, characterized in that The method comprises the following contents: (1) uniformly mixing an iron salt, an organic ligand, an organic high molecular polymer and a solvent to obtain a precursor mixture; (2) placing the precursor mixture in a sealed container for a solvent thermal reaction, cooling to room temperature after the reaction, separating the solid from the liquid, vacuum drying the solid particles, and then calcining them in an inert atmosphere to obtain a Fe / C complex; (3) adding the Fe / C complex to an appropriate amount of an aqueous solution containing an oxidant, and carrying out the liquid phase oxidation reaction under sealed conditions until the liquid phase oxidation reaction is fully carried out; (4) washing, drying, crushing and screening the obtained product to obtain a supported normal-parahydrogen conversion catalyst with a FeOOH / C structure.

6. The method according to claim 5, characterized in that: The material ratios in step (1) are, by weight, 1-10 parts of iron salt, 0.5-20 parts of organic ligand, 2-50 parts of organic high molecular polymer, and 50-150 parts of solvent.

7. The method according to claim 5, characterized in that: The iron salt described in step (1) is one or more of ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric nitrate or ferrous nitrate.

8. The method according to claim 5, characterized in that: The organic ligand in step (1) is one or more of fumaric acid, terephthalic acid, aminoterephthalic acid, trimesic acid, aminoimidazole or 2-methylimidazole.

9. The method according to claim 5, characterized in that: The solvent in step (1) is one or more of ethanol, N,N-dimethylformamide, dimethyl sulfoxide or water.

10. The method according to claim 5, characterized in that: The organic high molecular polymer in step (1) is one or more of polyvinyl pyrrolidone, polymethyl acrylate, chitosan, polyacrylic acid, sodium citrate, sodium oleate, polyethylene glycol or polyethylene glycol with carboxyl groups at both ends.

11. The method according to claim 5, characterized in that: The reaction temperature of the solvent thermal reaction in step (2) is 60-230° C., and the reaction time is 3-30 hours.

12. The method according to claim 5, characterized in that: The vacuum drying temperature in step (2) is 60-150° C., the vacuum drying time is 6-30 hours, and the vacuum degree is (-0.1)-(-8) kPa.

13. The method according to claim 5, characterized in that: The calcination temperature in step (2) is 350-900° C., and the calcination time is 10-200 minutes; the inert atmosphere is an inert gas and / or nitrogen.

14. The method according to claim 5, characterized in that: The oxidant in step (3) is hydrogen peroxide and / or peracetic acid.

15. The method according to claim 5, characterized in that: In step (3), the mass ratio of the Fe / C complex to the oxidant is 1:1-5, and the mass concentration of the oxidant used is 1-30%.

16. The method according to claim 5, characterized in that: In step (3), the liquid phase oxidation conditions of the Fe / C complex and the oxidant are: under autogenous pressure, reaction temperature 10-150° C., and reaction time 1-24 hours.

17. The method according to claim 5, characterized in that: The drying conditions of the catalyst in step (4) are: drying temperature 80-180° C., and drying time 3-48 hours.

18. Use of the FeOOH / C para-hydrogen conversion catalyst according to any one of claims 1 to 4 in a para-hydrogen conversion reaction.

Citation Information

Patent Citations

  • Coal liquefaction catalyst and preparation method and application thereof

    CN104923231A

  • High-stability ordered mesoporous carbon loaded Fenton catalyst, and preparation method and application thereof

    CN106853370A

  • FeOOH / carbon cloth heterogeneous Fenton catalyst with high specific surface area and preparation method of catalyst

    CN107497431A

  • Catalyst for catalyzing ortho-parahydrogen conversion as well as preparation method and application of catalyst

    CN114367288A

  • Porous nano-structured catalyst for ortho- to para-hydrogen conversion and method for preparing the same

    KR1020180129085A